Bioinspired Continuum Robots with Programmable Stiffness by Harnessing Phase Change Materials (Adv. Mater. Technol. 6/2023). Issue 6 (24th March 2023) - Zhang, Jie; Wang, Bo; Chen, Haohan; Bai, Jianing; Wu, Zhigang; Liu, Ji; Peng, Haijun; Wu, Jianing
Abstract : Bioinspired Continuum Robots In article number 2201616, Ji Liu, Haijun Peng, Jianing Wu, and co‐workers present a three‐segment continuum robot constructed by a class‐3 tensegrity structure, inspired by the mechanism of an elephant trunk for regulating local stiffness. It relies on a stiffness tunable material to achieve the robotic stiffness programmable characteristics. This study may provide a foundation for the potential application of continuum robots for interacting with unstructured environments.